(untitled) (Agricultural Engineering, 2019)
Conclusions on the analysis of the state of development in the tractor industry are formulated, aspects of the forecasting concept of transformation, general layout solutions and the theory of promising tractor units with new propulsion systems are considered, a general approach to the pre-design substantiation of new generation tractors is presented.